Inflammatory markers in relation to long-term air pollution. (August 2015) - Mostafavi, Nahid; Vlaanderen, Jelle; Chadeau-Hyam, Marc; Beelen, Rob; Modig, Lars; Palli, Domenico; Bergdahl, Ingvar A.; Vineis, Paolo; Hoek, Gerard; Kyrtopoulos, Soterios Α.; Vermeulen, Roel
Abstract: Long-term exposure to ambient air pollution can lead to chronic health effects such as cancer, cardiovascular and respiratory disease. Systemic inflammation has been hypothesized as a putative biological mechanism contributing to these adverse health effects. We evaluated the effect of long-term exposure to air pollution on blood markers of systemic inflammation. We measured a panel of 28 inflammatory markers in peripheral blood samples from 587 individuals that were biobanked as part of a prospective study. Participants were from Varese and Turin (Italy) and Umea (Sweden). Long-term air pollution estimates of nitrogen oxides (NOx ) were available from the European Study of Cohorts for Air Pollution Effects (ESCAPE). Linear mixed models adjusted for potential confounders were applied to assess the association between NOx and the markers of inflammation. Long-term exposure to NOx was associated with decreased levels of interleukin (IL)-2, IL-8, IL-10 and tumor necrosis factor-α in Italy, but not in Sweden. NOx exposure levels were considerably lower in Sweden than in Italy (Sweden: median (5th, 95th percentiles) 6.65 μg/m 3 (4.8, 19.7); Italy: median (5th, 95th percentiles) 94.2 μg/m 3 (7.8, 124.5)). Combining data from Italy and Sweden we only observed a significant association between long-term exposure to NOx and decreased levels of circulating IL-8. We observed some indication for perturbations in the inflammatory markers due to long-term exposure to NOx . Effects were stronger in Italy than in Sweden, potentially reflecting the difference in air pollution levels between the two cohorts. Highlights: We assessed the association between long-term exposure to NOx and plasma concentration of a panel of inflammatory markers. We included data from two prospective cohorts from Italy and Sweden (n=587 individuals). Our panel of inflammatory markers includes 28 cytokines, chemokines, and growth factors. We used a state of the art long-term air pollution exposure assessment developed within the ESCAPE project. We observed indications for an association between NOx and interleukin 2, 8, 10, and tumor necrosis factor alpha.